Effect of Savings Deposit Rate on Stock Market Capitalization in Nigeria: An Empirical Investigation - Eze, Gbalam Peter; Johnny, Nelson (International Journal of Business, Economics and Management, 2020)
This research plan is prepared to find out the impact of savings deposit rate on security market capitalization in Nigeria. The inquiry plan employed monthly data between January 2016 and December 2019. The data were collected from the publications of the National Bureau of Statistics (NBS) and Central Bank of Nigeria (CBN). Variables on which data were sourced are stock market capitalization (MCAP), savings deposit rate (SDR) and bank lending rate (BLR) as a control variable. The data analysis was done via descriptive tools, Johansen cointegration test, ADF test of unit root and regression procedure. The investigation discovered a significant inverse association among savings deposit rate and security market capitalization. The research also discovered insignificant negative link between bank lending rate and stock market capitalization in Nigeria. The overall equation judging from the R2, Durbin-Watson statistics and F-statistics is significant. It is thus recommended that, at anytime the country intend to raise the level of stock market capitalization, government should formulate and implement policies to reduce savings deposit rate in Nigeria. Government should also implement policies to reduce bank lending rate to boast economic growth and as well raise the level of stock market capitalization in Nigeria.